POTENSI ANTIBAKTERI EKSTRAK DAUN UBI JALAR UNGU (Ipomea batatas L.) TERHADAP BAKTERI GRAM NEGATIF DENGAN METODE BROTH MICRODILUTION - Siti Hamidatul Aliyah (JURNAL BIOSENSE, 2022)
Abstract Indonesia has wide cultivation of purple sweet potatoes (Ipomea batatas L.) commodities, particularly in Jambi province. However, the difference of phytochemical profiles in purple sweet potatoes among geographical regions has not been fully explored. The objective of this research to find out antibacterial activity of ethanol extract leaves purple sweet potato against bacteria Salmonella sp. and Pseudomonas aeruginosa. This study used Broth microdilution with concentration of 2 mg/mL, 4μg/mL, 8 mg/mL, 16 mg/mL, 32 mg/mL, 64 mg/mL, 128 mg/mL, 256 mg/mL, 512 ug/mL,1024 mg/mL. Chloramphenicol used as a positive control at the same concentration, minimum inhibitory concentration (MIC) determination made by the 50 seen from the transmittance value the test bacteria and minimum bactericidal concentration (MBC) by the determination of the lowest concentration in which no visible bacterial growth. Based on the test microbroth dilution leaves purple sweet potatoes had antibacterial activity against Salmonella sp. and Pseudomonas aeruginosa with MIC 64 mg/mL in Salmonella sp. and 128 ug/mL Pseudomonas aeruginosa. KBM obtained 512 mg/mL in Salmonella sp. and 512 ug/mL Pseudomonas aeruginosa.